Automation Process of Data Entry Using Robotic Process Automation - Mohd Fakhri, Nur Aliaa Syaza (IRC, 2020)
Robotic process automation (RPA) are used and implement in many sectors of industries which also include business enterprise to automate daily manual and repetitive task with almost thousands of data can be automate. The RPA implement rule-based process to adapt with the flexibility of the tasks. This project demonstrates the feasibility of RPA by providing efficient way of centralized all the of FYP details among the students in selected department and courses. This project shows a workflow of solution in improvement of data entry for the FYP information among the students. Throughout FYP 1, the author implements the SDLC (System Development Life Cycle) methodology. The methodology is consisting of planning phase, analysis phase, design phase and implementation phase. The implementation improvement solution was conducted with data gathering, data analysis and solution development which compare the current workflow with the proposed workflow by implementing the automation into the workflow. Thus, this can help to reduce the manual clerical and repetitive task and save cost and time taken to complete the task.